Experimental study on physical properties of superfine cement grouting material - Yu, Weijian; Zhou, Mingjuan; Wan, Xing; Guan, Qingjun (Frontiers in Materials, 2022)
In this paper, the properties of superfine cement with different mesh sizes are observed from both macro and micro perspectives through laboratory tests, and the fluidity, stability, and mechanical properties of superfine cement are studied in depth. The results show that increasing the mesh size of superfine cement can reduce the influence of the water-cement ratio on slurry, reduce the fluidity of superfine cement, and enhance its stability. The strength of the superfine cement stone specimen will increase with the increase in cement mesh number, and the higher the mesh number, the shorter the time required for the superfine cement stone specimen to reach its maximum strength. Considering the performance, cost, and storage difficulty, the superfine cement with the mesh size of K700 is more cost-effective. Using K700 superfine cement grout can effectively reduce the impact of geostress on the surrounding rock of the roadway and inhibit the deformation and damage of the surrounding rock.